The First Campaign and the Paradoxical Transformation of Fundraising in American Higher Education, 1915–1925. Issue 7 (July 2014) - Kimball, Bruce A.
Background: Comprehensive, multi-year mass fundraising campaigns in American higher education began with the Harvard Endowment Fund (HEF) drive, which extended from 1915 to 1925. Notwithstanding this prominence, the archival records of the campaign have never been studied closely, and in the absence of archival research, scholars have misunderstood the HEF campaign. According to the received and presentist view, the university president initiated the HEF campaign, which professional consultants then directed to a swift and successful conclusion, drawing on their expertise. Focus of study: The fundamental purpose was to learn from the archives what actually happened in this pathbreaking campaign. The research soon revealed that the unpaid organizers had to negotiate virtually all aspects of this novel venture among competing and conflicting groups of alumni, units of the university, and university administrators, including the president. The purpose then became to understand the divergent values and interests of the participants and how those perspectives contributed to the new goals, strategies, tactics, and practices introduced by the campaign. Setting: The research was conducted primarily in the Harvard University Archives and the Special Collections of Harvard Business School library. Research Design: The archival records comprise some fifty three boxes containing about forty thousand unindexed sheets of letters, memos, drafts, minutes, accounts, pamphlets, and other materials reposited in the Harvard University Archives. A chronological and topical examination of these materials over the past five years provides the research for this essay, which also draws upon a review of related collections in the Harvard University Archives and the Special Collections of Harvard Business School library. Conclusions: The research led to several surprising conclusions: that the landmark campaign failed to meet its goal, that professional consultants did not organize or run the campaign but emerged from it, that now long-standing features of university fundraising resulted less from deliberate planning than from contentious negotiations among conflicting groups, that the campaign prompted the university administration to centralize and control alumni affairs and development efforts for the first time, and, above all, that a central ideological tension arose between mass fundraising and the traditional approach of discretely soliciting wealthy donors. The unintended and unofficial outcome was to establish today's ubiquitous episodic pattern of continuous fundraising, in which mass comprehensive campaigns alternate with discrete solicitations of wealthy donors, whose dominant roles have never changed.